Diagnostic Accuracy of Unenhanced Low-Dose Multidetector Computed Tomography in Suspected Cases of Acute Appendicitis - Abdullah, Mashroof; Aziz, Tariq; Dildar, Nazia; Nisar, Uzma; Javed, Imran Ullah; Hussain, Gulzar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the diagnostic accuracy of unenhanced low-dose multi-detector computed tomography (LDMDCT) in detecting acute appendicitis, taking histopathology as the gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Radiology, Combined Military Hospital Rawalpindi, Pakistan, from May to Nov 2025. Methodology: A total of 92 patients aged 18–40 years presenting with clinically suspected Acute Appendicitis were enrolled using non-probability consecutive sampling. All patients underwent unenhanced LDMDCT on a GE Optima 128-slice scanner with radiation dose maintained below 3 mSv. CT findings were evaluated against histopathological diagnosis of resected appendix specimens. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated. Results: The mean age was 27.4±6.8 years, and 58(63.0%) participants were male. Histopathology confirmed acute appendicitis in 51 (55.4%) patients. Unenhanced LDMDCT demonstrated sensitivity of 88.2% (95% CI: 76.1–95.6%), specificity of 87.8% (95% CI: 73.8–95.9%), PPV of 90.0%, NPV of 85.7%, and overall diagnostic accuracy of 88.0%. No statistically significant difference in diagnostic accuracy was observed across gender or age subgroups (p>0.05). Conclusion: Unenhanced LDMDCT is a reliable and radiation-conscious imaging modality with high diagnostic accuracy for suspected acute appendicitis. Its routine adoption in emergency imaging pathways is strongly recommended to reduce unnecessary surgery and curtail radiation burden in the predominantly young population affected by this condition.